Development of an E-Ticketing Application to Improve Service Accessibility at Pudak Beach and as an Implementation of Muslim-Friendly Tourism in Ngadipuro Village, Wonotirto District, Blitar Regency - Moh Farih Fahmi; Moch Khoirul Anwar; Sri Abidah Suryaningsih; Rahmad Syaifudin (Journal of Islamic Economy and Community Engagement, 2025)
This community engagement program was implemented in Ngadipuro Village, Wonotirto District, Blitar Regency, an area with high tourism potential due to its strategic location along the South Ring Road and its abundance of coastal attractions. Despite this potential, the village has not yet achieved optimal tourism development, as reflected in its low SDGs indicators, limited digitalization, and weak institutional capacity of the local tourism group, Pokdarwis Dewata Puro. This program aimed to strengthen tourism governance through digital innovation, halal tourism development, and capacity building for local stakeholders. Using the Community-Based Research (CBR) approach, the program involved collaborative problem identification, intervention design, implementation, and evaluation with community partners. Key activities included the trial use of the Alamkuindonesia.com e-ticketing system, the creation of a halal tourism map supported by halal certification for local MSMEs, and a series of training sessions on tourism digitalization and financial management. The results show significant improvements in participants’ knowledge, as demonstrated by increased post-test scores, enhanced operational skills in digital tourism tools, and stronger awareness of halal tourism principles. The program also strengthened multi-stakeholder collaboration between the university, Pokdarwis, and partner organizations. Overall, this community service initiative successfully improved digital capacity, financial literacy, and halal tourism readiness in Ngadipuro Village. These outcomes indicate that integrated digital solutions and community empowerment strategies can support sustainable tourism development and contribute to improving village SDGs performance. The findings also provide implications for future research on digital-based tourism governance and collaborative models for rural tourism developmen